Reflection on the condition of women during the partition of India in the selected works of Sadat Hassan Manto - Juthi, Zarin Tasnim (Brac University, 2020)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2019.